Change in UK construction: moving toward supply chain collaboration - Meng, Xianhai (Journal of Civil Engineering and Management, 2013)
The traditional adversarial relationship in the construction industry has been criticized by a larger number of researchers and practitioners. Following the success of the supply chain collaboration in other industry sectors, such as manufacturing, supply chain relationships in UK construction have been increasingly changing from the traditional adversarial to the collaborative, which is supported by a series of government reports for the industry reform. However, few empirical studies have been conducted to investigate the current status of supply chain relationships in a systematic way. Therefore, there is no clear understanding of how change has taken place in today’s practice and whether or not the change is balanced. To bridge the gap, a questionnaire survey is carried out in the UK construction industry. Based on the analysis of more than 100 responses, it is found that the UK construction industry as a whole has experienced an important change and moved toward supply chain collaboration. On the other hand, an unbalance is found for the change movement. In addition to the questionnaire survey, a series of industrial experts are interviewed, which help to explore the specific characteristics of supply chain collaboration in construction and provide practical implications for collaboration strategy implementation.